2021
DOI: 10.1021/acsanm.0c02888
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Polymeric Nanoparticles Modified with a Protease-Resistant Peptide Shuttle for the Delivery of SN-38 in Diffuse Intrinsic Pontine Glioma

Abstract: Diffuse intrinsic pontine glioma (DIPG) is a chemo-resistant, incurable pediatric tumor of the central nervous system (CNS). The blood−brain barrier (BBB) remains intact in the course of the disease, preventing drugs from entering the brain and resulting in therapeutic failure. The topoisomerase I inhibitor SN-38 shows strong anticancer activity in a patient-derived DIPG cell line in vitro, though a low CNS bioavailability and anti-DIPG efficacy in vivo. In this work, we produced SN-38-loaded polymeric nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…To increase CNS bioavailability, the authors designed SN-38 loaded NPs of amphiphilic chitosan (CS)-g-poly (methyl methacrylate)-poly (acrylic acid) copolymer that was surface-modified with peptide to improve BBB transport. Their results confirmed the anti-DIPG efficacy of SN-38 NPs to kill almost 85% of stem-enriched DIPG cells and to successfully cross the BBB endothelium (in vitro) [ 82 ]. A dual targeting of CSCs niche (via curcumin) and bulk tumor cells (via doxorubicin) were developed by Xu and colleagues in the context of a glioma tumor.…”
Section: Relevant Cargoes For Brain Cscsmentioning
confidence: 60%
“…To increase CNS bioavailability, the authors designed SN-38 loaded NPs of amphiphilic chitosan (CS)-g-poly (methyl methacrylate)-poly (acrylic acid) copolymer that was surface-modified with peptide to improve BBB transport. Their results confirmed the anti-DIPG efficacy of SN-38 NPs to kill almost 85% of stem-enriched DIPG cells and to successfully cross the BBB endothelium (in vitro) [ 82 ]. A dual targeting of CSCs niche (via curcumin) and bulk tumor cells (via doxorubicin) were developed by Xu and colleagues in the context of a glioma tumor.…”
Section: Relevant Cargoes For Brain Cscsmentioning
confidence: 60%
“…In a previous work, we demonstrated that the permeability of fluorescently labeled dextran (average molecular weight of 40,000 g/mol, 0.001% w/v), a probe used to estimate the tightness of the BBB endothelium in vitro, is in the same range measured for other dextrans (Bukchin et al, 2020(Bukchin et al, , 2021. Based on immunostaining and RNA-Seq data, we anticipated that BBB endothelial cells cultured in 5-cell spheroids display even lower permeability than those in 2D monoculture systems.…”
Section: Interaction Of Nanoparticles With 5-cell Spheroidsmentioning
confidence: 76%
“…Our previous investigations conducted with primary rat cells suggested that neither forebrain nor olfactory neurons internalize polymeric NPs (Kumarasamy and Sosnik, 2019) and that, without the surface modification with a peptide shuttle, some of them cross the BBB in vitro and in vivo to a limited extent (Bukchin et al, 2020(Bukchin et al, , 2021. Conversely, they were internalized by primary microglia in vitro (Kumarasamy and Sosnik, 2019).…”
Section: Interaction Of Nanoparticles With 5-cell Spheroidsmentioning
confidence: 97%
“…17 These nanocarriers have been profusely investigated in the targeted treatment of cancer and other diseases by different administration routes. [18][19][20][21] Their surface can also be engineered to selectively bind specific receptors overexpressed by macrophages (e.g., mannose receptor, C-type lectin-like receptor), facilitating their uptake through various energy-dependent pathways. 22 Galactomannans (GMs) are natural nonionic biocompatible and biodegradable polysaccharides of b-(1-4)-linked b-D-mannopyranose backbone with single 1-6-linked a-D-galactopyranose branches 23,24 and it has been granted the ''generally recognized as safe'' status by the US Food and Drug Administration and thus, has found applications in the food, pharmaceutical and biomedical industries.…”
Section: Introductionmentioning
confidence: 99%
“…17 These nanocarriers have been profusely investigated in the targeted treatment of cancer and other diseases by different administration routes. 18–21 Their surface can also be engineered to selectively bind specific receptors overexpressed by macrophages ( e.g. , mannose receptor, C-type lectin-like receptor), facilitating their uptake through various energy-dependent pathways.…”
Section: Introductionmentioning
confidence: 99%